(untitled) (Altre Modernità, 2019)
Julián Axat, an Argentine poet whose parents disappeared during the 1976-83 military dictatorship, is also a journalist, editor of poetry and defense attorney for marginalized and delinquent minors from poor neighborhoods. In an arch that goes from the victims of State terror in the 1970s to the victims of police brutality and judicial indifference today, Axat’s poetry addresses the existence of those who, in Giorgio Agamben’s formulation in Homo sacer, are viewed as bare life, lives that are disposable and not worth living. Axat makes connections between treating certain individuals as bare life then and now in order to show a common thread between authoritarian practices of the military regime and those of neoliberal democracy. Poetry thus becomes the tool by which to oppose and denounce the continuity of social practices that deprive some of their human condition.